A statistical approach to estimating effects of performance shaping factors on human error probabilities of soft controls. (October 2015) - Kim, Yochan; Park, Jinkyun; Jung, Wondea; Jang, Inseok; Hyun Seong, Poong
Abstract: Despite recent efforts toward data collection for supporting human reliability analysis, there remains a lack of empirical basis in determining the effects of performance shaping factors (PSFs) on human error probabilities (HEPs). To enhance the empirical basis regarding the effects of the PSFs, a statistical methodology using a logistic regression and stepwise variable selection was proposed, and the effects of the PSF on HEPs related with the soft controls were estimated through the methodology. For this estimation, more than 600 human error opportunities related to soft controls in a computerized control room were obtained through laboratory experiments. From the eight PSF surrogates and combinations of these variables, the procedure quality, practice level, and the operation type were identified as significant factors for screen switch and mode conversion errors. The contributions of these significant factors to HEPs were also estimated in terms of a multiplicative form. The usefulness and limitation of the experimental data and the techniques employed are discussed herein, and we believe that the logistic regression and stepwise variable selection methods will provide a way to estimate the effects of PSFs on HEPs in an objective manner. Highlights: It is necessary to develop an empirical basis for the effects of the PSFs on the HEPs. A statistical method using a logistic regression and variable selection was proposed. The effects of PSFs on the HEPs of soft controls were empirically investigated. The significant factors were identified and their effects were estimated.